Struktur Komunitas dan Sebaran Populasi Kutu Putih (Hemiptera: Pseudococcidae) pada Tanaman Ubi Kayu di Bali: Implikasi Pengelolaan Hama Berkelanjutan - Astuthi, Made Mika Mega; Marsadi, Dicky; Dirgayana, I Wayan (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2025)
Mealybugs (Hemiptera: Pseudococcidae) are important pests that threaten cassava in Bali; however, detailed information on their community structure and spatial distribution remains limited. This study aimed to analyze the community structure and spatial distribution patterns of mealybugs infesting cassava across Bali Province, Indonesia. Field sampling was conducted in nine regencies—Jembrana, Tabanan, Buleleng, Badung, Denpasar, Gianyar, Bangli, Klungkung, and Karangasem—using a diagonal sampling method. In each regency, five sampling units were established, with five cassava plants observed per unit. On each plant, three upper, middle, and lower leaves were examined. The results of the study showed four mealybug species: Phenacoccus manihoti, Paracoccus marginatus, Ferrisia virgata, and Pseudococcus jackbeardsleyi, with species richness index values ranging from 0.368 to 0.388. All species were recorded in all surveyed regencies and exhibited a predominantly random spatial distribution pattern, as indicated by a variance-to-mean ratio (S²/X ≈ 1). Overall dominance was highest for P. marginatus (46.23%), particularly in Karangasem, followed by P. manihoti (45.72%) in Denpasar. The mealybug community structure was characterized by a diversity index (H′) ranging from 0.73 to 1.22, an evenness index (E) ranging from 0.16 to 0.24, and a dominance index (C) ranging from 0.32 to 0.54, indicating spatially variable communities that ranged from relatively stable to less stable conditions. These findings provide the baseline data on the community structure and spatial distribution of mealybugs on cassava in Bali, offering important insights for developing targeted monitoring and sustainable pest management strategies